Antigen discovery: a postgenomic approach to paratuberculosis diagnosis195 - Leroy,B.; Virginie Roupie; Noel-Georis,I.; Rosseels,V.; Walravens,K.; M. Govaerts; K Huygen; Wattiez,R. (Proteomics., 2007)
Paratuberculosis is a chronic enteritis caused in domestic and wild ruminant species by Mycobacterium avium subsp. paratuberculosis (MAP) that is responsible for major economic losses to the agricultural industry. To date, no satisfactory therapeutic, vaccine, or diagnostic tools are available, globally impairing all control programs. In this study, we have undertaken a large-scale postgenomic analysis of MAP proteins, to identify specific antigens that could potentially improve the diagnosis of paratuberculosis. Two complementary approaches were implemented, the first one consisting in the systematic proteomic identification of proteins present in MAP culture filtrates (CFs), followed by the selection of MAP-specific proteins by BLAST query on available mycobacterial genomes. The resulting database represents the first established secretome of MAP and a useful source of potentially specific antigens. The second approach consisted in the immunoproteomic analysis of both MAP extracts and CFs, using sera from MAP-infected and uninfected cattle. Combining results obtained with both approaches resulted in the identification of 25 candidate diagnostic antigens. Five of these were tested in an ELISA assay for their diagnostic potential, on a limited panel of field sera, and the combination of three of them competed in performance with available commercial assays, reaching a test sensitivity of 94.74% and specificity of 97.92%
Keywords: 0; a; ALL; an; analysi; analysis; Animals; Antigens; Antigens,Bacterial; approach; approaches; article; Bacterial Proteins; Belgium; Cattle; Cattle Diseases; chemistry; chronic; Combination; Control; culture; Database; Diagnosis; Domestic; ECONOMIC; Enzyme-Linked Immunosorbent Assay; Field; Genome; identification; identify; im; immunology; improve; Industries; Industry; IS; isolation & purification; journal; map; Mycobacterium; Mycobacterium avium subsp.paratuberculosis; ON; Paratuberculosis; performance; present; Print; PROGRAM; Programs; protein; Proteins; Proteomics; Research; Research Support; result; results; SB - IM; Selection; SENSITIVITY; serum; Species; specific; specificity; study; Test; Universities; university; vaccine